Who is at the table? Civic engagement in small town housing decision-making. Issue 6 (2nd November 2021) - Odeyemi, Ebunoluwa; Skobba, Kimberly
ABSTRACT: Small towns possess many of the components needed for stakeholder-led governance models, including strong social ties, frequent interactions and social norms that support participation in civic life. This study seeks to better understand civic engagement with housing decision-making in rural small towns. We examine the diversity of actively engaged stakeholder groups and the ways in which stakeholder participation is related to community characteristics using survey responses from representatives of 164 small towns within one Southeastern state. For the small towns in our study, population size, limited administrative capacity and access to human capital resources were associated with fewer engaged stakeholder groups. Relatively few stakeholder groups were involved in housing decision-making on average and those experiencing the greatest disadvantage were likely not at the table. This research adds to the limited body of research on civic engagement by exploring stakeholder engagement in housing decisions and policies in small towns using a unique dataset. Our study highlights the ways in which the potential for civic engagement in small towns is hindered, limiting the capacity and equity of housing policy among rural communities that likely have an array of housing problems. Understanding how and why local governments in small towns engage stakeholder groups for housing planning and decision-making is an area for future research.